Counterion effects on nano-confined metal–drug–DNA complexes - Biswas, Nupur; Chakraborty, Sreeja; Datta, Alokmay; Sarkar, Munna; Mukhopadhyay, Mrinmay K.; Bera, Mrinal K.; Seto, Hideki (Beilstein Journal of Nanotechnology, 2016)
We have explored morphology of DNA molecules bound with Cu complexes of piroxicam (a non-steroidal anti-inflammatory drug) molecules under one-dimensional confinement of thin films and have studied the effect of counterions present in a buffer. X-ray reflectivity at and away from the Cu K absorption edge and atomic force microscopy studies reveal that confinement segregates the drug molecules preferentially in a top layer of the DNA film, and counterions enhance this segregation.
Keywords: confinement; metal–drug–DNA composites; polyelectrolyte; X-ray scattering